Preparation of prolinamide with adamantane for aldol reaction catalysis in brine and separation using a poly(AN-MA-β-CD) nanofibrous film via host–guest interaction. Issue 50 (7th August 2018) - Wang, Rui; Xu, Enjie; Su, Zhenming; Duan, Haifeng; Wang, Jinjin; Xue, Longqi; Lin, Yingjie; Li, Yaoxian; Wei, Zhonglin; Yang, Qingbiao
Abstract : Prolinamide with adamantane catalyzed the aldol reaction. The reaction of cyclohexanone with m -nitrobenzaldehyde assessed recyclability of catalyst. After run, the catalyst was adsorbed with nanofibrous of polymer via host–guest interaction. Abstract : Prolinamides with double-H potential were prepared and employed as organocatalysts in asymmetric aldol reactions. The catalyst with adamantane showed improved catalytic activity, which was further enhanced by using brine as the solvent. A series of aldol reactions in brine at 0 °C provided good yields (up to 98%) with high diastereoselectivities (>99 : 1) and enantioselectivities (>99%). The prepared catalyst was adsorbed by a nanofibrous film of poly(AN-MA-β-CD) via host–guest interaction in the reaction system. The catalyst was separated from the film by applying ultrasound, with a total recovery of 96.2%. The catalyst was reused up to five times without a significant change in diastereoselectivity and enantioselectivity.